Aboriginal and Torres Strait Islander disability prevalence: making sense of multiple estimates and definitions - Clare Coleman; Nicola Wing Young Man; John Gilroy; Richard Madden (Elsevier, 2018)
Abstract Objective: To analyse the multiple sources of statistics on prevalence of disability among Aboriginal and Torres Strait Islander (Indigenous) people in Australia to provide reliable headline estimates. Methods: Survey documentation and statistics from the Australian Bureau of Statistics (ABS) were collated and comparatively analysed. Results: Two separate concepts are defined by the ABS: 'Disability' and 'Disability and restrictive health conditions'. The former is used in the Survey of Disability, Ageing and Carers (SDAC), the recommended source of disability prevalence estimates. The second is used in surveys to compare people with disability to those without. The 2014-15 National Aboriginal and Torres Strait Islander Survey (NATSISS) used a mix of these definitions, which led to differing prevalence estimates from SDAC estimates. Further, there is confusion in the NATSISS results, with 'disability' frequently replacing 'disability and restrictive health condition'. Discussion: The SDAC should be used for prevalence statistics on disability in the Indigenous population. The ABS should act to clarify or withdraw confusing results from the 2014-15 NATSISS survey. Implications for public health: Official statistics are used to allocate resources; in particular, to and within the National Disability Insurance Scheme. These need to be accurate to ensure Indigenous people's health needs are met.